Medicinal and aromatic plant collection of Baccharis dracunculifolia DC. germplasm bank - Belini, C. M. B. [UNESP] (2016)
The collection of medicinal and aromatic plants (CPMA) at the University of Campinas, Campinas, Brazil was started in 1989 and in 2005 the Federal Ministry of Environment accredited CPMA as a depository of genetic heritage. CMPA consists of a seed bank (in vitro preservation and in vivo or ex situ conservation), herbarium, DNA bank, database, and active germplasm banks from species or genera with potential interest for the development of cultivars. In addition to providing didactic opportunities, the CPMA plays a vital role in seed storage, genetic conservation, exchange of genotypes, and distribution for producers and researchers. Presently, the introductions are from different regions of Brazil and other continents with 2,444 accessions (1,546 species and 156 botanic families). One of the plants of major interest in the CPMA is Baccharis dracunculifolia (Asteraceae), a native and widely distributed shrub that develops rapidly and can be potentially used in restoration programs as a successful colonizer of poor, acid soils. It is also the source of green propolis, a natural resinous substance collected from buds and exudates of B. dracunculifolia, produced by honeybees (Apis mellifera). To evaluate the diversity in B. dracunculifolia, several accessions have been genotyped using simple sequence repeat markers. The results showed little genetic diversity, despite genotyping collections from three different regions of natural occurrence in Brazil. Presently, a strategy to acquire new collections in areas of extreme altitudes has been adopted in the hope of finding diversity amongst members of the species.